Reconsidering the Forres cross-slab (Sueno’s Stone), part 2: iconography - Geddes, Jane (Proceedings of the Society of Antiquaries of Scotland, 2024)
Standing over 6.5m high, the Forres cross-slab (NJ 04655 59533), erroneously known as Sueno’s Stone, is Scotland’s tallest early medieval carved stone monument. One side features a cross and ‘inauguration’, the other is covered with multiple military scenes. A new carbon date from the 9th century, 3D photography and an accurate suite of new drawings allow the iconography of the stone to be examined in detail. This reveals the ‘inauguration’ as an adaptation of the biblical Arming of David. The episodic arrangement of battle is compared to verses of heroic poetry rather than accurate reportage. The sacrifice of horses beside headless corpses relates the encounter to Viking funeral practice. The conical structure is interpreted as the furnace of hell, destination for unbelievers. The cross form and other ornament relate clearly to a Pictish heritage but their composition looks forward to later sculpture evolving in the west and Isle of Man. Complementing archaeological and historical evidence, the cross-slab is understood as a mighty affirmation of Christian kingship and victory at a time of shifting power structures in north-east Scotland.